The Phytochemical Analysis of Hay Infusions and Papaya Leaf Juice as an Attractant Containing Insecticide for Aedes Aegypti (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Aedes aegypti mosquito population could be controlled by using lethal ovitrap. The addition of hay infusions as a attractant greatly enhance Aedes aegypti eggs trapped, and papaya leaf juice may inhibit Aedes aegypti eggs evolve to larvae or a larvae to pupae stage. This study was conducted to find out the chemical compounds in hay infusion and papaya leaf juice. We used phytochemical test using UV-Vis Spectrophotometry, Thin Layer Chromatography, and High Performance Liquid Chromatoraphy (HPLC) method. The results showed that hay infusion contains 12,75 mg/L ammonium and 1,20 ppm (µg/mL) lactic acid and papaya leaf juice contains 0,25% alkaloid, 0,14% flavonoid, 0,30% saponin, ≤68 mg/L steroid and 11,34% tannin, but negative terpenoid. We concluded that hay infusion and papaya leaf juice contains chemical compounds that could be use as attractant and bioinsecticide to Aedes aegypti, respectively.